Pre‐Rift Orogenic Erosion Facilitates the Exhumation of Lower Crust at Rifted Margins - Kai Li; Sascha Brune; Zoltán Erdős; Xiaoping Yuan; Anne Glerum; Christian Berndt; Peter Haas (Geophysical Research Letters)
Abstract During the late‐stage of continental rifting, lower crustal rocks can be exhumed to the Earth's surface. Such exposure has been identified especially in rifts that developed within former orogens. These rifts exploited zones of lithospheric weakness created during previous mountain‐building events. Here we investigate whether lower crustal exhumation during rifting could result directly from structural inheritance of prior orogeny. To this aim we use Wilson‐Cycle numerical models where we impose a prior shortening and subsequent extension. Our models incorporate the effects of thermal and structural inheritance as well as surface processes. We find that the erosion of mountain belts thins the upper crust, reducing the upper‐to‐lower crustal ratio prior to rifting. This process facilitates the exhumation of lower crustal material during extension, exposing them at the Earth's surface along the footwall of normal faults. We suggest a new conceptual model to explain lower crustal exhumation observed at rifted margins worldwide.